Therapeutic Modulation of Haematological Parameters and Fertility Outcomes in Postpartum Subclinical Endometritis in Jaffarabadi Buffaloes - Kapadiya, Pratik S; Vala, Karsan B; Parikh, Suryakant S; Vijyeta, Hardipsinh P; Sharma, Arun K; Savsani, Harish H (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present study investigated the effects of intrauterine lysozyme, povidone iodine, and antibiotic therapy on haematological parameters  and conception rates in postpartum subclinical endometritic (SCE) Jaffarabadi buffaloes. Thirty animals (24 SCE-affected and 6 healthy  controls) were randomly allocated into five groups: Group I (lysozyme 2 mg in 20 mL PBS once), Group II (2% povidone iodine, 50 mL  once), Group III (sensitive antibiotic, levofloxacin, 20 mL for 3 days), Group IV (untreated positive control), and Group V (healthy negative  control). Haemoglobin, packed cell volume, total leukocyte count, and differential leukocyte counts (neutrophils, lymphocytes, monocytes,  eosinophils, basophils) were assessed at 0 h, 72 h, and at subsequent estrus. Conception rate was evaluated on the basis of first service  conception (FSCR) at subsequent estrus. Groups I and II buffaloes exhibited significant (p
Keywords: Conception rate, Haematological parameters, Intrauterine therapy, Jaffarabadi buffalo, Lysozyme, Povidone iodine, Subclinical endometritis